The impact of using competitive training methods on developing some basic skills for futsal juniors under 15 years old - Hamza, L. Ali Hashm; Hussain, Dr. Muhamad Ali; Abass, Prof.Dr. Aujad Mlul (Sulaimani Journal for Humanities, 2026)
This study aims to develop a competitive training program to enhance the skills of young futsal players and to determine the impact of this program on their skill development. The research hypothesis is that the proposed training program has a positive effect on developing certain skills in young futsal players, and that there are significant differences between the pre-test and post-test scores, favoring the experimental group. The researchers employed an experimental design (two groups: a control group and an experimental group) using pre- and post-testing. The research population consisted of young futsal players under 15 years old at Al-Hashemiya Sports Club during the 2023-2024 season. Simple random sampling was used to select the sample, which comprised 18 players: 9 in the control group and 9 in the experimental group. The main findings are: 1- A clear improvement was observed in both the control and experimental groups across the research variables. 2- The experimental group, which utilized competitive training methods, demonstrated superior development across the research variables. 3- Using any training method may positively affect the basic skills of young futsal players.
Keywords: Competition style; basic skills; football